PHYTOCHEMICAL SCREENING OF FIELD-GROWN PLANTS AND in vitro TISSUE CULTURE OF Hovenia dulcis THUNB - GONÇALVES RIBEIRO, IVAN; CARVALHO DE CASTRO, TATIANA; MACHADO GAYER, CARLOS ROBERTO; GARCIA PINTO COELHO, MARSEN; ALBARELLO, NORMA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
Hovenia dulcis Thunberg is a tree which belongs to the family Rhamnaceae and is known in Brazil as “uvado-japão”. Many species of Rhamnaceae have been investigated for medicinal properties and important pharmacological activities were reported, such as those related to malaria treatment and the prevention of Chagas Disease. Among the several medicinal studies from the Rhamnaceae species, antioxidant, hepatoprotective, antimicrobial, antineoplasic and antigiardic activities were reported. The aim of this study was to carry out phytochemical screening of leaves from a wild growing plant and compare to material produced from biotechnological methods based on tissue culture. The HPLC analysis revealed that plants grown under field conditions presenting more diverse chromatographic profile and indicating the presence of a large quantity of compounds. Gas chromatography showed that these extracts presented higher amounts of volatile compounds. Moreover, the absence of peaks in samples from calli and in vitro propagated plants suggests that volatile compounds are not present in these samples. Due to the differences observed in the phytochemical profiles, according to their origin, the data reinforce the use of in vitro technologies for compounds production, being able to produce secondary metabolites not found in the field plant, or allowing in vitro manipulation of these compounds.